Rule‐based requirements management methodology. Issue 3 (15th February 2013) - Kotejoshyer, Badari; Singh, Birendra; Tittibha, Suhas; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
ABSTRACT This paper proposes a methodology to identify and prevent/control noncompliances and conflicts arisingout of requirement attribute values during requirements management. It is intended to provide a cost‐effective approach for managing noncompliances in projects that employ the requirements based engineering approach. The method involves continuous checking and monitoring of requirement attribute values using a rule‐based engine concept. This methodology can serve as an enhanced feature for any commercial requirement management application software available today (such as IBM DOORS© and Seimens TcSE©).The methodology offers the following advantages: It enables standardization in the development and management of requirement modules. It decreases development and maintenance cost for requirement modules by reducing the effort needed for audits, compliance checks, rework and others. Copyright © 2013 John Wiley & Sons, Ltd.